2020
DOI: 10.1007/s11442-020-1828-2
|View full text |Cite
|
Sign up to set email alerts
|

Building national eco-cultural protection areas and the Xiangxi practice in Hunan Province

Abstract: Since 2007, the Chinese government has initiated the building of national eco-cultural protection areas (NECPAs), thereby embarking on a significant transformation of the model of intangible cultural heritage (ICH) protection in China. To understand the origin and outputs of this policy, this paper demonstrates the context of China's NECPAs. It proposes a conceptual NECPA framework that mainly features regional overall ICH protection. This is followed by an examination of the case of Xiangxi in Western Hunan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The differentiation is affected by the complexity, diversity, nonlinearity and heterogeneity of each influencing factor [31]. Basic qualitative analysis and single factor exploration are difficult to accurately quantify the interaction between the factors affecting the distribution of traditional villages [19]. Therefore, exploring the spatial distribution characteristics of traditional villages through reasonable statistical analysis means can master the human land interaction mechanism of villages and establish scientific protection and continuation policies, which is of great significance to the construction of ecological civilization and the protection of local cultural heritage and cultural diversity [32].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation is affected by the complexity, diversity, nonlinearity and heterogeneity of each influencing factor [31]. Basic qualitative analysis and single factor exploration are difficult to accurately quantify the interaction between the factors affecting the distribution of traditional villages [19]. Therefore, exploring the spatial distribution characteristics of traditional villages through reasonable statistical analysis means can master the human land interaction mechanism of villages and establish scientific protection and continuation policies, which is of great significance to the construction of ecological civilization and the protection of local cultural heritage and cultural diversity [32].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, most of the current research methods are based on ArcGIS spatial autocorrelation analysis, combined with residual analysis or correlation analysis; However, residual analysis cannot quantify the analysis factors [19], while correlation analysis can quantify but not express spatial heterogeneity. It is suggested that [20].…”
Section: Introductionmentioning
confidence: 99%
“…1). Geographically positioned between longitudes 109° 10′ E to 112° 15' E and latitudes 25° 44′ N to 29° 47′ N, it adjoins the Yunnan-Guizhou Plateau to the west and the Dongting Lake Plain to the east [30]. The region is traversed by the Wuling and Xuefeng Mountains, extending from the southwest to the northeast, which imparts a predominantly mountainous landscape.…”
Section: Study Areamentioning
confidence: 99%
“…The Tujia region in Western Hunan is often located in a mountainous and complex terrain, and ancient towns often stand by water, such as the ancient towns on both sides of the You River region, which are adjacent to waterway transportation hubs, forming a developed commercial trade space. By contrast, Tujia villages lack a large amount of commercial trade space, and the homes are often built on hillsides, forming many stilted buildings [52]. Due to the differences in terrain, production methods, and other factors between Tujia villages and ancient towns, their residential architecture differs considerably:…”
Section: Ancient Tujia Towns In Western Hunanmentioning
confidence: 99%